Evaluation of Fill Pack Damage to the Cooling Effectiveness of Counter Flow Type Cooling Tower in the Oil and Gas Industry - Roihatin, Anis; Nabila Aida Az Zahro (Eksergi, 2024)
In the oil and gas industry, cooling water is needed to cool various kinds of heat-generating equipment and as a backup water requirement. Cooling water in the industry is usually produced by cooling towers in large quantities. The working principle of the cooling tower by exchanging heat from the hot water of a process with exhaled cold air. There is a cooling tower part called a fill pack and has an important function as a place for heat exchange between water and air. In this research in the oil and gas industry, the cooling tower used is a wet cooling tower type with counter flow flow. The purpose of this study is to determine the current cooling effectiveness of the cooling tower compared to its design data. Calculating the effectiveness of cooling certainly requires water temperature data produced by the cooling tower. The method used in this research is the method of taking water temperature data before and after leaving the cooling tower. The level of cooling effectiveness in the cooling tower will be better if the water temperature produced is cooler than the water temperature when entering the cooling tower.